A hybrid technique for evaluating the trust of cloud services - Trabay, Doaa; Asem, Azezza; El-Henawy, Ibrahim; Gharibi, Wajeb (International journal of information technology (Singapore. Online), 2021)
Cloud computing has become a common desire as an alternative for investing in new IT systems. Every day, more agencies benefit from the services reachable in the cloud. Due to the large storage of information and data in the cloud, concerns about customer confidence or trust in the cloud increase as cloud services have been increased. Given the diversity of cloud service providers, identifying the appropriate cloud services, including trust, which meets organizations requirements, is one of the main challenges in cloud computing. This paper builds a mathematical model to evaluate trust from various opinions based on performance, agility, finance, security, and usability criteria using a hybrid fuzzy logic method and multi-criteria decision-making techniques. By comparing the results obtained with others, it appears that our results are more efficient for organizations and users.